Quantitative Analysis Of Heat Transfer On Human Operator Using Thermal Models - Maniyan, Suresh (2007)
An effort has been made in this thesis to estimate the time for fatigue of a human operator based on the workload. Workload in turn depends on the condition of the operator and environmental conditions, which is reflected in the muscle temperature. Simple yet comprehensive mathematical models for heat transfer in human body were developed for both steady as well as transient states. Conduction, convection, radiation, and evaporation modes of heat transfer were considered in the models. The models were also validated against the results available in the literature. Parametric studies involving the condition of the operator and the environment were also carried out. From the mathematical model muscle temperature required for the estimation of the time for fatigue of the operator was determined. Three case studies from a multinational company were considered which involve different types of task. The time for fatigue has been estimated for the three cases by mathematical calculation and compared with the actual time for fatigue of the operator, which is obtained from by interviewing the operators. It is observed that for these case studies the estimated value and also the actual value are in close agreement, e.g. case study 1 estimated value of time to fatigue is 0.56 minute and actual time to fatigue is 0.6 minute which shows that the calculated value is in close agreement with the actual value. Similarly for case study 2 the calculated value is 0.15 minute in compared to the actual value of 0.18 minute. The same result was also obtained for case study 3 whereby the actual result is 0.22 minute versus the predicted value of 0.26 minute. As the predicted value and the actual time are in close agreement it has been proposed that the same type of analysis can be expanded to other fatiguing tasks across the industry.